Modified Polyethylene Oxide Solid-State Electrolytes with Poly(vinylidene fluoride-hexafluoropropylene) - Jinwei Yan; Wen Huang; Tangqi Hu; Hai Huang; Chengwei Zhu; Zhijie Chen; Xiaohong Fan; Qihui Wu; Yi Li (Molecules)
Lithium-ion batteries are restricted in development due to safety issues such as poor chemical stability and flammability of organic liquid electrolytes. Replacing liquid electrolytes with solid ones is crucial for improving battery safety and performance. This study aims to enhance the performance of polyethylene oxide (PEO)-based polymer via blending with poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)). The experimental results showed that the addition of P(VDF-HFP) disrupted the crystalline regions of PEO by increasing the amorphous domains, thus improving lithium-ion migration capability. The electrolyte membrane with 30 wt% P(VDF-HFP) and 70 wt% PEO exhibited the highest ionic conductivity, widest electrochemical window, and enhanced thermal stability, as well as a high lithium-ion transference number (0.45). The cells assembled with this membrane electrolyte demonstrated an excellent rate of performance and cycling stability, retaining specific capacities of 122.39 mAh g−1 after 200 cycles at 0.5C, and 112.77 mAh g−1 after 200 cycles at 1C and 25 °C. The full cell assembled with LiFePO4 as the positive electrode exhibits excellent rate performance and good cycling stability, indicating that prepared solid electrolytes have great potential applications in lithium batteries.